ANALISIS PELAKSANAAN MANAJEMEN RISIKO DI INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH TUGUREJO SEMARANG TAHUN 2018 - Khansa Maghfira Djatnika; Septo Pawelas Arso; Sutopo Patria Jati (Jurnal Kesehatan Masyarakat (Undip), 2019)
Risk management is an activity to identify, assess, and formulate risk priorities proactively with the aim of eliminating or minimizing the impact of risk, as well as an effort to improve the quality and patient safety purposes. Secondary data shows that the Pharmacy Installation of Tugurejo Hospital Semarang consists of high-risk services. The study aims to analyze the implementation of risk management at Pharmacy Installation of Tugurejo Hospital Semarang. Research variables are context establishment, risk assessment, risk treatment, monitoring and review, and communication and consultation. This research is a qualitative descriptive study using in-depth interviews and document review. The results of the study show that risk management in the Pharmacy Installation of the Tugurejo Regional General Hospital is still ineffective based on ISO 31000: 2009 standard anylisis. Researcher found incongruity in the studied variables which are generally caused by weak communication and consultation and also weak monitoring and review which only focused on the risk treatment stage when it is supposed to be done at all stages of risk management. Recommended that Pharmacy Installation should improve internal communication and hospital management should be to be more committed in providing feedback and monitoring the risk management sustainability in the work unit.